2017
DOI: 10.1111/evo.13302
|View full text |Cite
|
Sign up to set email alerts
|

Body size evolution in an old insect order: No evidence for Cope's Rule in spite of fitness benefits of large size

Abstract: We integrate field data and phylogenetic comparative analyses to investigate causes of body size evolution and stasis in an old insect order: odonates ("dragonflies and damselflies"). Fossil evidence for "Cope's Rule" in odonates is weak or nonexistent since the last major extinction event 65 million years ago, yet selection studies show consistent positive selection for increased body size among adults. In particular, we find that large males in natural populations of the banded demoiselle (Calopteryx splende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 101 publications
(206 reference statements)
3
80
0
Order By: Relevance
“…A recent review of body size evolution in the Odonata found a consistent trend of positive selection for larger size, but at the same time no evidence for an increase in body size over evolutionary time. The authors suggested that this lack of concordance is due to the trade-off between larger body size as adults and longer larval life (Waller and Svensson, 2017). Survivorship seems more related to body size for JSBS males than for females (compare the slopes in fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of body size evolution in the Odonata found a consistent trend of positive selection for larger size, but at the same time no evidence for an increase in body size over evolutionary time. The authors suggested that this lack of concordance is due to the trade-off between larger body size as adults and longer larval life (Waller and Svensson, 2017). Survivorship seems more related to body size for JSBS males than for females (compare the slopes in fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that survival may show interannual variation, a suggestion that also merits further study. It seems likely that contrasting selective regimes between natural and sexual selection in adults, between larvae and adults (Waller and Svensson, 2017), and between years and localities contributes to the stasis observed on body size over time.…”
Section: Discussionmentioning
confidence: 99%
“…Heteragrion cooki: Rivas-Torres, et.al, 2017; Polythore mutata; Cordero-Rivera et al, unpublished), and similar results were also found in other taxa, such as the mosquito Aedes aegypti (Maciel-De Freitas, et.al, 2007). Large size is favoured in adult odonates, but probably not in larvae, contributing to the stasis in body size observed over evolutionary time (Waller & Svensson, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…ExN50 ~ 3kb), suggesting sufficient data for a high quality assembly. We also estimated the OHR of our assembly by querying our assembly with the full protein set of the only published odonate genome, the banded demoiselle damselfly (Calopteryx splendens), which shared a common ancestor with I. elegans approximately 85 million years ago (the average from two dated phylogenies, 92 Ma in Thomas et al 2013 and 79 million years in Waller and Svensson 2017). Of the 22,507 C. splendens proteins that were non-redundant, we found good hits (e-value less than 10e-5) for roughly 19,962, and of these, we found OHR of 0.7 and higher for nearly 70% (13,497; see Fig.…”
Section: Reference Transcriptomementioning
confidence: 99%